(3CMcGe GdfLhes - (3jMji Hf eMeO Hf CHj GdTcQ, eMjj GdOjf, CHh GdaJM, hjYQa HGdMcje GdeZQHj , GHf CHj GdoqTrcQ , J fMh (B680 (3g`s
(3ChdgG (B:s
(3JHOC HHGH ai WhGdY GdSfjf ZPG cGf WGdY GdSfI HQL GdMed aEf GdeSJOd YdjgG GdTeS s
(3BNQgG (B:s
(3GdHGH GdKGdK hGdYTQhf GdMce Ydi GdEfJgGA ef WGdY GdbQBf GdOGd Ydi GdedI GdESdGejI hajeG PcQfG caGjI hGddg CYde hCMcGe HGdUhGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs